4 - On HIV, Sex and Respect: Local-Global Discourse Encounters among the Datoga ofTanzania - Astrid Blystad (African Sociological Review, 2004)
The topic of concern in this paper is the manner in which global/y constructed AIDS and HIV control messages are received by the Datoga of Tanzania. The text will rejlect on how messages on safe and healthy sex in national/global HIV campaigns are not in accord with Datoga concepts and practices aimed at ensuring proper sexuality and fertility, and the troubled eflècts of such dissonance. In an attempt to grasp the dynamics at work in the encounters between HIV prevention messages and local sexual concepts and practices, some central Foucauldian questions are asked, such as how and why sexual activity is constituted as a moral domain among Datoga. The substantial Datoga preoccupation with procreation is located at the heart of the argument. The discussion will reveal how Datoga sexuality is becoming increasingly troubled, compounding and accentuating the already severe uncertainties experienced in everyday lifè. The argument is o.ffered that unless communication about HIVIAIDS takes the cultural contexts that shape risk behaviour into account, such campaigns will fall on deaf ears, and may cause more su.f fering rather than less.